111k views
1 vote
Simplify the following equations please:)

1. 2n - 4 + 6n
2. -15 + 9m
3. 19a - 7 - 3a + 12a
4. 6(x - 3) + ( 2x - 9)
5. (3x + 8) - 6 (2.5x - 3)

1 Answer

2 votes

Answer:

1. n = 1/2

2. m = 5/3 or 1 2/3

3. a = 1/4

4. x = 27/8

5. x = 13/6

Explanation:

I'm just going to explain step 5 as that is what you specifically needed help with.

First, simplify the second term of the equation:

-6(2.5x-3)

= -15x + 18

(this was done by multiplying -6*2.5x which is 15x and -6(-3) which is 18)

Now, add this simplified second term back to the first term:

3x + 8 - 15x + 18

(the parentheses are unnecessary now because it is all just addition and subtraction, so the order doesn't matter)

Simplify:

-12x + 26 = 0

= -12x = -26

= x = -26/-12

= x = 13/6

User Neonidian
by
5.1k points